Oxygen-evolving photosynthetic cyanobacteria for 2D bismuthene radiosensitizer-enhanced cancer radiotherapy - Chai, Rong; Yu, Luodan; Dong, Caihong; Yin, Yipengchen; Wang, Sheng; Chen, Yu; Zhang, Qin (Bioactive materials, 2022)
The local hypoxic tumor environment substantially hampers the therapeutic efficiency of radiotherapy, which typically requires the large X-ray doses for tumor treatment but induces the serious side effects. Herein, a biomimetic radiosensitized platform based on a natural in-situ oxygen-evolving photosynthetic cyanobacteria combined with two-dimensional (2D) bismuthene with high atomic-number (Z) components, is designed and engineered to effectively modulate the radiotherapy-resistant hypoxic tumor environment and achieve sufficient radiation energy deposition into tumor. Upon the exogenous sequential irradiation of 660 nm laser and X-ray beam, continuous photosynthetic oxygen evolution by the cyanobacteria and considerable generation of reactive oxygen species by the 2D bismuthene radiosensitizer substantially augmented the therapeutic efficacy of radiotherapy and suppressed the in vivo tumor growth, as demonstrated on both LLC-lung tumor xenograft-bearing C57/B6 mice model and 4T1-breast tumor xenograft-bearing Balb/c mice model, further demonstrating the photosynthetic hypoxia-alleviation capability and radiosensitization performance of the engineered biomimetic radiosensitized platform. This work exemplifies a distinct paradigm on the construction of microorganism-enabled tumor-microenvironment modulation and nanoradiosensitizer-augmented radiotherapy for efficient tumor treatment. [Display omitted] •The unique microorganism-based and 2D bismuthene-mediated biomimetic radiosensitization platform has been engineered for enhanced tumor nanotherapy.•The photosynthetic production of oxygen has been utilized via natural microorganism cyanobacteria to effectively modulate the radiotherapy-resistant hypoxic tumor environment with high biocompatibility.•The biomimetic dual-radiosensitized platform has achieved sufficient radiation energy deposition for inducing overproduction of reactive oxygen species to augment the RT efficacy.